2022
DOI: 10.3390/jpm12081203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex on Mortality in Patients Undergoing Surgical Aortic Valve Replacement

Abstract: Aortic stenosis (AS) is the second most common valvular heart disease in the United States. Although the prevalence of AS does not significantly differ between the sexes, there is some controversy on whether sex differences affect the long-term mortality of patients with severe AS undergoing surgical aortic valve replacement (SAVR). Therefore, we retrospectively analyzed the medical records of 917 patients (female, n = 424 [46.2%]) with severe AS who had undergone isolated SAVR at a tertiary care center betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Ten-year mortality ranged from 10.0 to 44.1% for men and 11.0 to 39.1% for women 23,24,27,29,31,33,35 . One study found a significant difference in survival at 10 years, with 44.1 and 30.0% mortality rates for men and women who received bioprosthetic aortic valve replacements, respectively ( P < 0.0001), but no difference in mortality for those who had received mechanical SAVR ( P = 0.74) 28 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Ten-year mortality ranged from 10.0 to 44.1% for men and 11.0 to 39.1% for women 23,24,27,29,31,33,35 . One study found a significant difference in survival at 10 years, with 44.1 and 30.0% mortality rates for men and women who received bioprosthetic aortic valve replacements, respectively ( P < 0.0001), but no difference in mortality for those who had received mechanical SAVR ( P = 0.74) 28 .…”
Section: Resultsunclassified
“…Intraoperative parameters Significant differences in the distribution of prosthesis type between the sexes was noted in eight studies, with six reporting significantly more women undergoing AVR with a bioprosthesis. 21,24,25,27,29,35 Overall, 18-88.2 and 19.4-89.5% of men and women received a bioprosthesis after excluding one study that solely included patients who underwent mechanical SAVR. 31 Cardiopulmonary bypass and/or aortic-cross clamp times were reported in eight studies.…”
Section: Overview Of Aortic Valve Studiesmentioning
confidence: 99%
See 1 more Smart Citation